Case 3777: Clausilia index Mousson, 1863, Clausilia semilamellata Mousson, 1863, Clausilia derasa Mousson, 1863 (Gastropoda, Stylommatophora, Clausilidae): proposed precedence of the specific names over three objective synonyms, Clausilia unilamellata Mousson, 1856, Clausilia multilamellata Mousson, 1856 and Clausilia firmata Mousson, 1856 - Walther, Frank; Hausdorf, Bernhard (Bulletin of Zoological Nomenclature, 2018)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the specific names Clausilia index Mousson, 1863, Clausilia semilamellata Mousson, 1863 and Clausilia derasa Mousson, 1863, for three terrestrial snail species (family Clausiliidae) by suppressing the unused senior synonyms Clausilia unilamellata Mousson, 1856, Clausilia multilamellata Mousson, 1856 and Clausilia firmata Mousson, 1856, respectively.
Keywords: Nomenclature; taxonomy; Gastropoda; Stylommatophora; Clausiliidae; Mucronaria; Index; Pravispira; Elia; Caucasus